Institutional barriers to learning in the South African open distance learning context - Mashile, E.O.; Fynn, A.; Matoane, M. (South African Journal of Higher Education, 2020)
The discourses surrounding student success and risk have shifted emphasis from the concept of risk as residing with student attributes, aptitudes and socio-economic history to the concept of contextualized risk, which is a result of the interaction between student, institution and the broader higher education context. This shift in discourse has led to a change in understanding the role that institutions play in “creating” at-risk students through institutional culture, procedures, policies and assumptions about the nature of teaching and learning. Institutional barriers to learning have received relatively little attention in the scholarship of teaching and learning when compared to the wider body of research on student-bound risk factors. Institutional barriers to learning refer to those institutional characteristics that, when combined with the attributes of the student body, create inadvertent barriers to successful study completion. This article makes use of frameworks derived from prior research into the barriers to learning and established models of student support to identify what students perceive as institutionally embedded barriers to teaching and learning in an institution in the South African open, distance and e-learning context.